GM1 Gangliosidosis: Mechanisms and Management - Rha, Allisandra K (Appl Clin Genet, 2021)
The lysosomal storage disorder, GM1 gangliosidosis (GM1), is a neurodegenerative condition resulting from deficiency of the enzyme β-galactosidase (β-gal). Mutation of the GLB1 gene, which codes for β-gal, prevents cleavage of the terminal β-1,4-linked galactose residue from GM1 ganglioside. Subsequent accumulation of GM1 ganglioside and other substrates in the lysosome impairs cell physiology and precipitates dysfunction of the nervous system. Beyond palliative and supportive care, no FDA-approved treatments exist for GM1 patients. Researchers are critically evaluating the efficacy of substrate reduction therapy, pharmacological chaperones, enzyme replacement therapy, stem cell transplantation, and gene therapy for GM1. A Phase I/II clinical trial for GM1 children is ongoing to evaluate the safety and efficacy of adeno-associated virus-mediated GLB1 delivery by intravenous injection, providing patients and families with hope for the future.